Transforming the 'mainstream' : Gol & Gincu / Benjamin McKay - McKay, Benjamin (UPENA, 2007)
There has been a steady increase in the number of independent films produced in Malaysia over the last five years. Those films have often challenged the manner in which Malaysia and Malaysians are portrayed on the screen. The independent film movement in Malaysia has directly challenged the core mainstream commercial cinema in that country, by utilising languages other than Bahasa Melayu and by reflecting upon the lives of non-Bumiputera Malaysians and the manner in which they connect (or otherwise) with their ethnic Malay fellow citizens. This essay explores the opportunities open to mainstream Malaysian cinema by adopting the spirit of the vibrant independent filmmaking community.